311. Modeling Diagnostic Testing Strategies for SARS-CoV-2 to Minimize Societal Costs and Return People to Work. (15th December 2022) - Zavala, Sofia; Cox, Gary M; Belknap, Robert W; Smith, Becky A; Lewis, Sarah S; Polage, Christopher R; Turner, Nicholas A; Stout, Jason E
Abstract: Background: The shift to more transmissible but less virulent strains of SARS-CoV-2 has altered the risk calculation for infection. Particularly among young adults, the economic burden of lost work due to isolation exceeds the economic burden of morbidity due to infection. Testing strategies must adapt to these changing circumstances. Methods: We modeled six testing strategies to estimate total societal costs for symptomatic people 18-49 years old: isolation of all individuals with no testing, rapid antigen test (RAg), RAg followed by a second RAg 48h later if first negative, RAg followed by a polymerase chain reaction (PCR) if negative, RAg followed by a PCR if positive, and PCR alone. We calculated costs for hypothetical cohorts of 100 symptomatic healthcare workers tested with each strategy; we included testing costs, lost wages, and hospitalization costs for the index, secondary, and tertiary cases. Key assumptions were 5% prevalence of infection, sensitivity of first/second RAg 40/80% with 97% specificity, PCR sensitivity/specificity 95/99%, all individuals isolate at symptom onset, are tested the same day, and isolate for 5 days if positive. RAg results were available the same day, PCR results were available the next day (Figure 1). One-way sensitivity analyses were performed for RAg sensitivity (20-80%) and positivity rate (1-80%). Results: The least expensive strategy was RAg alone (Figure 2). This was primarily driven by its low sensitivity, which reduced lost wages at the expense of missing cases. At a threshold for RAg sensitivity lower than 29%, PCR testing alone became the cheapest strategy. When the positivity rate was > 6% confirming a negative RAg with a PCR became the cheapest strategy, closely followed by PCR alone. At a positivity rate of > 29%, isolation without testing was cheapest followed by confirming a negative RAg with a PCR and by the serial RAg test strategies (Figure 3). Conclusion: In relatively young, healthy populations, a single rapid test was the least expensive strategy when the positivity rate was < 6%, testing that included PCR became cheapest at intermediate positivity, and empiric isolation was cheapest at positivity > 29%. Calibrating SARS-CoV-2 test strategies based on epidemiology may save societal costs. Disclosures: Nicholas A. Turner, MD, MHSc, Aperio: Advisor/Consultant.